2007
DOI: 10.1007/s11262-007-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequence analysis of a nucleopolyhedrovirus isolated from the diamondback moth, Plutella xylostella

Abstract: The CL3 plaque isolate of Plutella xylostella multiple nucleopolyhedrovirus (PlxyMNPV-CL3) exhibits a high degree of genetic similarity with the Autographa californica MNPV (AcMNPV) but is significantly more virulent against the diamondback moth, P. xylostella, than AcMNPV. To identify genetic differences between PlxyMNPV-CL3 and AcMNPV that may account for the difference in virulence against P. xylostella, the genome sequence of the CL3 plaque isolate of PlxyMNPV was determined and compared to the genome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…Prior to sequencing, amplimers were precipitated away from excess primers and deoxynucleotides as previously described [27]. In some cases, amplimers were purified by agarose gel electrophoresis or cloned using the TOPO TA Cloning Kit (Invitrogen, Carlsbad, CA).…”
Section: Pcr and Sequencingmentioning
confidence: 99%
“…Prior to sequencing, amplimers were precipitated away from excess primers and deoxynucleotides as previously described [27]. In some cases, amplimers were purified by agarose gel electrophoresis or cloned using the TOPO TA Cloning Kit (Invitrogen, Carlsbad, CA).…”
Section: Pcr and Sequencingmentioning
confidence: 99%
“…The sequence that belongs to the ORF14 from BmMNPV had an identity of 99% with ORF23 of AcMNPV, which is related to viral folding protein (Gomi et al, 1999). It also had an identity of 88% with folding protein or F protein of PxMNPV (Harrison and Lynn, 2007), and with a folding protein of A. californica as well (Ayres et al, 1994). However, an identity of 84% was observed with a fusion protein of RoMNPV (Harrison and Bonning, 2003), whereas a 65% identity to MvMNPV was detected (Chen et al, 2008).…”
Section: Bmmnpv Orf10 and Orf14 Amino Acid Sequencesmentioning
confidence: 97%
“…The analysis of ORF14 nucleotide sequence revealed that the sequence of MNPV subgroup of B. mori (BmMNPV) had identity equivalent to 99, 94, 93, 89, 79%, respectively, with: BmNPV genome, isolate T3 (Gomi et al, 1999); AcMNPV genome, clone C6 (Ayres et al, 1994); PxMNPV genome, isolate CL3 (Harrison and Lynn, 2007); RoMNPV genome (Harrison and Bonning, 2003), and MvMNPV genome (Chen et al, 2008). …”
Section: Orf14 Sequence Analysismentioning
confidence: 99%
“…Two microlitres of a 100-fold dilution of the DNA templates was used in 50 ml PCRs as described by Rowley et al (2010) using primers designed to amplify the AdorGV ORFs p10, ORF 14, pep-p10, pep-2, ORF 30, p47, dbp, desmoplakin and AdorGV-E ORF 112 (Table S4). Amplimers were precipitated away from excess primers and nucleotides using 20 % PEG/2.5 M NaCl and subsequently sequenced with gene-specific primers as described by Harrison & Lynn (2007).…”
mentioning
confidence: 99%